Aumento acentuado da leucina como fator de mau prognóstico na doença da urina de xarope de bordo - relato de caso - Bruna Duque de Almeida Braga; Gessianni Claire Alves de Souza; Filipe Marinho Pinheiro da Camara; Ana Cecília Menezes de Siqueira; Lucas Victor Alves (Sociedade Brasileira de Pediatria, 2023)
INTRODUCTION: Leucinosis or Maple Syrup Disease (MSD) is an innate metabolism error caused by a deficiency in the activity of the alpha-keto acid-dehydrogenase enzyme complex, which leads to the accumulation of essential branched-chain amino acids (leucine, valine, and isoleucine), leucine is particularly toxic to the central nervous system (CNS). OBJECTIVES: Report a case of maple syrup disease in a 10-day-old newborn (NB), born to consanguineous parents, with late diagnosis, with high levels of leucine, with an unfavorable prognosis. COMMENTS: MSD is a rare condition, of autosomal recessive origin, which occurs due to the accumulation of essential branched-chain amino acids in tissues(leucine, valine, and isoleucine). The accumulation of amino acids mainly affects the CNS. Studies have shown that the elevated leucine concentration decreases the serum sodium concentration and increases intracellular water, causing cerebral edema. Neurological damage will depend on the degree and time of tissue exposure to metabolites. Despite the unfavorable outcome of the case presented, the prognosis of MSD can be modified with strict diet control and early and aggressive management of metabolic crisis.